(untitled) (Revista Apotheke, 2017)
Based on the concept of cartography as a methodological approach, this article deals with articulations between blind passion and love, regarding a research itinerary in four cultural institutes. The present loving writing weaves the quest for the object of research, through fragments and aporias that report a diving into the experience, and connects researcher and research object in the same composition plan. In this cartographic design, the desire to search is linked to the need of writing through another angle, creating a universe for a loving delight that states the loving speech.